NILAI–NILAI PENDIDIKAN KARAKTER DALAM KITAB AL-ADAB AL-MUFRAD KARYA AL-IMAM ABU ABDILLAH MUHAMMAD IBN ISMAIL AL-BUKHARI - Muchlis Nurseha; Sudarno Shobron; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2019)
Abstract: Character education has become a hot topic discussed by the community and the world of education lately, phenomena that have arisen in the community are the cause of such discussions, including; the spread of liquor and narcotics among adolescents, pornographic photos and videos that can be accessed by anyone without limits so that it has an impact on free sex, corruption cases of some unscrupulous state officials, from the lower levels to the state elite and other criminal cases. This kind of situation causes the Indonesian nation to experience moral degradation and a crisis of character, so it is necessary to look for solutions and solutions. Considering that the majority of Indonesian people are Muslim, al-Adab al-Mufrad is a book written by the expert of al-Imam al-Bukhari's hadith which specifically discusses adab, morals and character, is expected to provide a solution to the character crisis that is in the midst of society. The purpose of this study was to determine the values of character education contained in the book of al-Adab al-Mufrad and analyze the relevance of the values of character education contained in the book of al-Adab al-Mufrad with the values of the Ministry of National Education character. This type of research is a library research study that uses a qualitative paradigm with a philological or semantic approach. Research data were analyzed using content analysis methods. The results showed that the Book of al-Adab al-Mufrad by al-Imam al-Bukhari had mentioned all the values of character education contained in the Ministry of National Education, but the values of character education in the book of al-Adab al-Mufrad were more specific in the mention of these values, so they need to be grouped in order to be compatible with the values of the Ministry of National Education character. The character education values in the al-Adab al-Mufrad book are still relevant to the character education values developed by the Ministry of National Education, this is because the character education values developed by the Ministry of National Education have all been mentioned in the al-Adab al-Mufrad book.Abstrak: Pendidikan karakter menjadi tema yang hangat diperbincangkan oleh masyarakat dan dunia pendidikan akhir-akhir ini, fenomena yang muncul di tengah masyarakat menjadi sebab perbincangan tersebut, di antaranya; tersebarnya minuman keras dan narkotika di kalangan remaja, foto dan video porno yang dapat di akses siapa saja tanpa batas sehingga berdampak pada seks bebas, kasus korupsi beberapa oknum pejabat negara, mulai tingkat bawah sampai elit negara dan kasus-kasus kriminal lainnya. Keadaan semacam ini menyebabkan bangsa Indonesia mengalami degradasi moral dan krisis karakter, sehingga perlu dicarikan solusi dan jalan keluar. Mengingat sebagian besar masyarakat Indonesia memeluk agama islam, kitab al-Adab al-Mufrad merupakan kitab karangan pakar hadis al-Imam al-Bukhari yang khusus membahas seputar adab, akhlak dan karakter, diharapkan memberikan salah satu solusi krisis karakter yang ada di tengah masyarakat. Tujuan dari penelitian ini untuk mengetahui nilai-nilai pendidikan karakter yang terkandung dalam kitab al-Adab al-Mufrad dan menganalisis relevansi nilai-nilai pendidikan karakter yang terkandung dalam kitab al-Adab al-Mufrad dengan nilai-nilai pendidikan karakter Kemendiknas. Jenis penelitian ini merupakan penelitian library research yang menggunakan paradigma kualitatif dengan pendekatan philologis atau semantik. Data hasil penelitian dianalisis menggunakan metode content analisis. Hasil dari penelitian ini menunjukkan; pertama, Kitab al-Adab al-Mufrad karya al-Imam al-Bukhari telah menyebutkan semua nilai-nilai pendidikan karakter yang tertuang dalam Kemendiknas, akan tetapi nilai-nilai pendidikan karakter dalam kitab al-Adab al-Mufrad lebih spesifik dalam penyebutan nilai-nilai tersebut, sehingga perlu dikelompokkan agar dapat sesuai dengan nilai-nilai pendidikan karakter Kemendiknas. Kedua, nilai-nilai pendidikan karakter dalam kitab al-Adab al-Mufrad masih relevan dengan nilai-nilai pendidikan karakter kemendiknas, karena nilai-nilai pendidikan karakter Kemendiknas yang berjumlah delapan belas butir sudah disebutkan semua oleh al-Imam al-Bukhari dalam kitab al-Adab al-Mufrad.